Developing Asean5 Bond Markets : What Still Needs to Be Done? - Gray, Simon (IMF Working Papers; Working Paper ;, 2011)
This paper examines a range of issues relating to bond markets in the ASEAN5 (Indonesia, Malaysia, Philippines, Singapore and Thailand) - physical infrastructure including trading, clearing and settlement; regulation, supervision and legal underpinnings; and derivatives markets - and finds that the frameworks compare well with other Emerging Markets, following a decade of reform. A number of areas where further enhancements could be made are highlighted. The paper also examines the interrelationship between central bank management of short-term interest rates and domestic currency liquidity, and development of the wider money and bond markets; and suggests some lessons from the recent crisis in developed country financial markets which may be important for the future development of the ASEAN5 markets.